Outside Front Cover: Plasma Process. Polym. 11/2022. Issue 11 (4th November 2022) - Coad, Bryan R.; Favia, Pietro; Vasilev, Krasimir; Griesser, Hans J.
Abstract : Outside Front Cover : Plasma polymers have long been of interest as thin film coatings on biomedical devices and products, to generate desirable surface properties for favourable bio‐interfacial interactions. The cover image symbolically depicts plasma's versatility in its ability to modify biomedical surfaces for various purposes. From its role in fundamental research on cell‐interfacing surfaces and its use in modifying laboratory materials, plasma's utility is also apparent in the development of commercial healthcare products. This article is part of the virtual issue on Plasmas for Biointerfaces, volume 19, issue 10. Further details can be found in the article by Bryan R. Coad, Pietro Favia, Krasimir Vasilev, and Hans J. Griesser (e2200121 ) (© Image provided by Bryan Coad)